2008
DOI: 10.1103/physrevlett.100.014102
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Components in Narrow Planetary Rings

Abstract: The phase-space volume of regions of regular or trapped motion, for bounded or scattering systems with 2 degrees of freedom, respectively, displays universal properties. In particular, drastic reductions in the volume (gaps) are observed at specific values of a control parameter. Using the stability resonances we show that they, and not the mean-motion resonances, account for the position of these gaps. For more degrees of freedom, exciting these resonances divides the regions of trapped motion. For planetary … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…This power law arises from combined effects of an infinite hierarchy of islands with a corresponding hierarchy of time scales. Recent investigations of resonance splittings and homoclinic tangles in the vicinity of islands may provide insight into these mechanisms [25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…This power law arises from combined effects of an infinite hierarchy of islands with a corresponding hierarchy of time scales. Recent investigations of resonance splittings and homoclinic tangles in the vicinity of islands may provide insight into these mechanisms [25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…The stability resonances are defined by the occurrence of a resonant condition (a rational ratio of 2蟺) of the linear stability exponents of the central linearly stable periodic orbit. Therefore, they are related to the local stability properties of the central stable periodic orbit (Benet and Merlo 2008). Note that the stability resonances must not correspond to mean-motion resonances, which are defined as a rational ratio between the period of the central stable periodic orbit and the period of the disk.…”
Section: Two Degrees Of Freedom and Stability Resonancesmentioning
confidence: 99%
“…We observe that each ring component is related to a different region of the histogram. This is a consequence of the large gap opened by the 1:3 stability resonance, which effectively separates the phase space regions of trapped motion in two disjoint regions (Benet and Merlo 2008). Yet, while the 1:6 stability resonance widens up its corresponding gap, it does not separate enough the phase-space regions around it.…”
Section: Beyond Two Degrees Of Freedom: Strands and Arcsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the work done within the framework of chaotic scattering (or scattering in higher dimensions) deals with a static scattering potential. Recently, it has been found that complex behavior with different characteristics can be observed in scattering systems involving a time-dependent scattering potential [23,24,25,26,27,28,29]. As a representative example of such a system the scattering of freely moving, non-interacting particles off two hard, infinitely heavy, oscillating discs on the plane has been studied.…”
Section: Introductionmentioning
confidence: 99%